Experience with the use of handheld Doppler for fetal heart rate monitoring during coronavirus disease-19 pandemic - Bajpayee, Devina; Agrawal, Ritu; Dastidar, Sourav Ghosh; Bisht, Nitin; Panda, Ranjan Kumar; Kumar, Arvind; Sarin, Enisha; Kumar, Harish (Eastern Journal of Medical Sciences, 2020)
Background: Fetal heart rate (FHR) monitoring during intrapartum care is important; however, the use of Doppler during coronavirus disease (COVID-19) pandemic needs to be investigated especially in light of the enhanced infection prevention (IP) required during labor and childbirth. The present study was carried out to evaluate the experience of using a handheld Doppler having both continuous and intermittent monitoring features in seven health facilities across three states. Materials and Methods: Program data including case load, frequency of monitoring, and fetal outcome was obtained from January to March 2020 were compared with data during the lockdown period from April to June 2020. A semi-structured questionnaire was used for a telephonic qualitative interview of eight service providers from the seven facilities to supplement the quantitative data. Transcripts were analyzed using ATLAS.ti to find out how the Doppler was being used. Results: There was decrease in the case load during lockdown; however, there was no decrease in the frequency of monitoring. There was no difference on rate of abnormal FHR detected, stillbirths, and asphyxia. IP protocol was followed in all facilities. The handheld Doppler was used by four facilities to continuously monitor pregnant women. While, study participants reported that strapping the belt for continuous monitoring reduced exposure to suspected COVID cases, two participants believed that strapping could be a risk factor for transmission. Conclusion: Usage of the Doppler for FHR detection can be used for monitoring progress during labor using IP protocol.